The GWAS Analysis of Body Size and Population Verification of Related SNPs in Hu Sheep - Jiang, Junfang; Cao, Yuhao; Shan, Huili; Wu, Jianliang; Song, Xuemei; Jiang, Yongqing (Frontiers in Genetics, 2021)
Body size is an important indicator of growth and health in sheep. In the present study, we performed Genome-Wide Association Studies (GWAS) to detect significant single-nucleotide polymorphisms (SNPs) associated with Hu sheep's body size. After genotyping parental (G1) and offspring (G2) generation of the nucleus herd for meat production of Hu sheep and conducting GWAS on the body height, chest circumference, body length, tail length, and tail width of the two groups, 5 SNPs were identified as significantly correlated to body height and 4 SNPs as significantly correlated to chest circumference. There were no SNPs that were significantly correlated to body length, tail length, and width. Four out of the 9 SNPs were found to be located within the genes. KITLG and CADM2 can be treated as candidate functional genes related to body height in Hu sheep, while MCTP1 and COL4A6 as candidate functional genes related to Chest circumference in Hu sheep. The 9 SNPs found in GWAS were verified by using the G3 generation of the nucleus herd for meat production. Nine products were amplified around the 9 sites, and a total of 29 SNPs were found, of which 4 mutation sites were significantly correlated to the Hu sheep's body height. Dual-Luciferase reporter gene experiments showed that the 4 SNPs could significantly impact dual-luciferase and gene transcription activity.